2021
DOI: 10.3389/fpsyt.2021.562899
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Developing Post-traumatic Stress Disorder in Severe COVID-19 Survivors, Their Families and Frontline Healthcare Workers: What Should Mental Health Specialists Prepare For?

Abstract: Given the high mortality of the coronavirus disease 2019 (COVID-19), having severe COVID-19 may be a life-threatening event, especially for individuals at high risk of complications. Therefore, in the article we try to answer two questions that are relevant to public mental health: Can we define groups who are at higher risk of developing pandemic-related PTSD? How can health specialists prepare for it? Given the results of previous research on PTSD in epidemic (e.g., SARS) survivors, we suggest that mental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 35 publications
2
25
0
3
Order By: Relevance
“…However, in some people they may be a symptom of serious mental problems, requiring professional psychological care. Particularly prone to this stress are people who feel a real threat to their health or who have lost their jobs [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, in some people they may be a symptom of serious mental problems, requiring professional psychological care. Particularly prone to this stress are people who feel a real threat to their health or who have lost their jobs [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to comorbidities related to physical health, people with ED also experience the effects of the mental strain caused by COVID-19. Gradually there are studies that describe not only the impact of the pandemic and the threat of infection on the mental health [3,4], but also reports on the mental consequences of suffering from COVID-19 itself [25,26]. As it was shown, medical workers infected with COVID-19 significantly more often experienced deppresion, anxiety, intrusion, hypervigilance and avoidance than healthy medical workers [25].…”
Section: Impact Of Ed On Covid-19mentioning
confidence: 99%
“…As it was shown, medical workers infected with COVID-19 significantly more often experienced deppresion, anxiety, intrusion, hypervigilance and avoidance than healthy medical workers [25]. Persons with other mental problems [26] (e.g., ED) are at higher risk of developing PTSD as a consequence of being sick on COVID-19. Meta-analysis of studies according psychiatric symtoms of severe Coronaviral infection described delirium and altered consciousness [27].…”
Section: Impact Of Ed On Covid-19mentioning
confidence: 99%
“…It was due to lack of 'warmth", social and personal interactions, and engagement in virtual communication (Lee et al, 2011). Past research on the severe acute respiratory syndrome (SARS) epidemic found that the risk of post-traumatic stress disorder (PTSD) was high and this is to be expected to be the same post-COVID-19 (Sekowski et al, 2021). This is confirmed by psychiatrists from Oxford University that almost one in five coronavirus patients developed some mental illness within three months of being diagnosed with Covid-19 (Schladebeck, 2020).…”
Section: Movement Control Order (Mco)mentioning
confidence: 99%
“…This is confirmed by psychiatrists from Oxford University that almost one in five coronavirus patients developed some mental illness within three months of being diagnosed with Covid-19 (Schladebeck, 2020). Hence, proactive action should be taken by every individual, healthcare personnel should be warned of the risks of PTSD of COVID-19 survivors and be ready for the necessary therapeutic interventions (Sekowski et al, 2021).…”
Section: Movement Control Order (Mco)mentioning
confidence: 99%